A Philosophical Critique of Anthropocentrism and Environmental Decolonization in Raja Ampat’s Indigenous Territories - Jamaludin, Muhammad; Fauzi, Mohamad Rizal; Hapsari, Intan Dwi (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to examine the impact of mining industry expansion on customary territories in Indonesia, focusing on ecological and social aspects. Using a qualitative approach and a critical paradigm, this research seeks to uncover the power relations underlying extractivist practices and how they marginalize local communities while damaging the ecological systems that sustain their livelihoods. Data were collected through field studies, participatory observation, satellite imagery analysis, and a review of legal and policy documents. The study areas include several vulnerable small islands in Indonesia, such as Pulau Gag (West Papua), Pulau Wawonii (Southeast Sulawesi), and Pulau Gebe (North Maluku), as well as other regions such as Kalimantan, East Halmahera, Southwest Maluku, Riau Islands, and Bengkulu. The findings reveal that mining activities have led to significant environmental degradation, including deforestation, soil and water pollution, and the disruption of local biodiversity. Socially, mining has triggered the displacement of Indigenous communities, land conflicts, and the erosion of cultural practices rooted in harmonious relationships with nature. This analysis reinforces previous studies’ findings that extractive development models based on anthropocentrism and colonial logic are the leading causes of ecological crises and structural inequalities in Indigenous territories. The main contribution of this study is the articulation of a counter-narrative to the dominant technoscientific discourse in natural resource development. Through an interdisciplinary approach that integrates ecological, social, and cultural dimensions, this research highlights the urgency of decolonizing environmental governance toward a more just, participatory, and sustainable framework.